Zombie Fly (suggested common name) Apocephalus borealis Brues (Insecta: Diptera: Phoridae) - Nicole Casuso; Ashley N. Mortensen; James D. Ellis (EDIS)
The zombie fly is primarily a parasitoid of bumble bees and wasps in North America. In 2012, Dr. John Hafernik and his colleagus at San Francisco State University discovered that Apocephalus borealis also parasitizes honey bees. Parasitized honey bees show zombie-like behavior by leaving their hives at night and are often attracted to nearby lights where they show disoriented behavior and die in a few hours. This 5-page fact sheet was written by Nicole A. Casuso, Ashley N. Mortensen, and James D. Ellis, and published by the UF Department of Entomology and Nematology, October 2014. (Photo: Jessica Andrieux, CC SA-BY 2.5)